Application of the SNP-analysis for characterisation of Phytophthora infestans-isolates - Niepold, Frank (MTT, 2007)
Using the single nucleotid polymorphism (SNP) method P. infestans could be easily characterised. P. infestans-isolates collected in the period from 2000 to 2004 did show a continuous change of the chromosomal area used for the SNP analysis. At the end of the survey only 25% of the isolates corresponded with the original DNA sequence (230 bp fragment). Since a non-coding DNA region was used for the SNP analysis, genetic changes could easier be found within the surveyed period. For monitoring the genetic changes of P. infestans-isolates a host change was performed (potato-tomato respectively black nightshade). Parts of the surveyed P. infestans isolates showed a stable SNP-fragment of the proper size, being independently from the host change. The other part of the isolates did not only show visual microscopic differences in the sporangia but also in the detection of the 230 bp SNP-fragment. Since it is not plausible that in a highly variable gene a fast change via point mutation can occur that fast, it is assumed that in that case a population mixture was surveyed. Therefore, a stress in the form of a host change might favour the one or other P. infestans-isolate exhibiting a change in the SNP-fragment. When the P. infestans isolates grown on different hosts were re-inoculated onto their potato hosts, the acquired change in the SNP-pattern was kept.
Keywords: Ka